Técnicas de relajación psicofisiológicas para disminuir los niveles de agresividad infantil de los niños y niñas de 4 a 5 años de la escuela Dorotea Carrión de la ciudad de Loja. Periodo septiembre 2013 julio 2014 - Tocto Quituizaca, Claudia del Carmen (2015)
The present research of theoretical and practical entitled: PSYCHOPHYSIOLOGICAL RELAXATION TECHNIQUES TO REDUCE THE LEVEL OF AGGRESSIVENESS OF CHILDREN OF 4-5 YEARS OF SCHOOL DOROTEA CARRIÓN DE LOJA. SEPTEMBER 2013 PERIOD JULY 2014. Has been structured and developed in accordance with the Rules of Academic System of National University. Has set five objectives; general; To analyze the theoretical foundations of psychophysiological relaxation techniques and child aggression in children aged 4-5 years. And four specific: Determine the level of aggressiveness. Select psychophysiological relaxation techniques. Implement a Program psychophysiological relaxation technique. Validate the relevance of psychophysiological relaxation techniques to reduce levels of aggression in children of 4-5 years of school Dorotea Carrión de Loja. Synthetic, deductive inductive, descriptive, hermeneutic, analytical method, as instruments of observation and test of the Family, aimed at children in order to gather the necessary information and data used was used. According to the results obtained were determined that children have problems with aggression and through the application of the formula Pearson correlation moderate negative linear inverse relationship of -0.79 efficacy, where relaxation techniques help shown reduce aggression problems.